Students‘ Motivation on the Use of Technology and Its Relationship with Their Receptive Skills - Sulistyo, Bambang; Anggeraini, Yentri; Nurhasanah, Nurhasanah; Yusnilita, Nopa; Awalludin, Awalludin; Episiasi, Episiasi (Jurnal Pendidikan Progresif, 2023)
Students` motivation on the use of technology and its relationship with their receptive skills. Objective: to explain the link between English learners' motivation to use technology and their receptive (reading and listening) skills. Method: a correlation study was employed with 56 participants including freshman, sophomore, and junior students at Universitas Baturaja as selected through convenient sampling method. To gather the data, motivation questionnaire, reading test, and listening test were distributed and the instruments were valid and reliable. Result: students` motivation on the use of technology in learning significantly had a moderate correlation with their receptive skills (reading and listening). Conclusion: It can be derived that the EFL learners had high motivation for learning English by using technology and its relationship on their receptive skills was in a good category. Keywords: motivation, receptive skills, technology.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202320